Management of Abandoned Land in the Context of Poverty Alleviation in Aceh - Agustyarsyah, Agustyarsyah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2025)
Abstract: The purpose of this study is to investigate and analyse how the law is implemented in managing wasteland, as well as the challenges and solutions related to the enactment of Government Regulation Number 11 Year 2010 concerning land control and utilisation. This study includes a sociological study of law (non-doctrinal) that involved descriptive research. The fourth-law concept is a pattern of social behaviour that has been created as an empirical variable in this study. The method of collecting data in this study is literature study and using qualitative data analysis as a data analysis method. Based on the findings, the wasteland in Aceh is managed by Baitul Mal and land offices. The wasteland management method that has been used is farming activities. Therefore, the implementation of this method can be applied to increase the local community's income and also eradicate poverty issues. Keywords: Government Regulation, Poverty, Reform, Wasteland